Analysis of Qurban and Aqiqah Savings Products of KSPP Syariah BMT “Nashrul Ummah” Balen as a Solution in Planning Qurban and Aqiqah for Customers - Syaifudin, Ahmat Arif; Khoiriyah, Ni’matul (Journal of social Philantrophy and Halal Research, 2024)
This study aims to determine the effectiveness of the qurban and aqiqah savings products of KSPP sharia BMT "Nashrul Ummah" Balen as a solution in planning qurban and customer aqiqah. descriptive qualitative approach. Sources of research data used are: observation, documentation, observation, and documentation. direct interview with BMT Nasrul Ummah Balen. BMT Nasrul Ummah’s efforts to prove the effectiveness of Qur’an and aqiqah savings products as a solution in planning customer qurban and aqiqah are quite effective and efficient for customers by planning to save a certain amount per week or per month within a specified period of time until there is sufficient funds to perform qurban or aqiqah.